Pengaruh Trust Dan Word Of Mouth Terhadap Loyalitas, Peran Mediasi Kepuasan Pelanggan Pengguna Shopee - Ahmad Fa’izin Syahputra (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of Word of Mouth (WOM) promotion and trust on Shopee customer loyalty in Lamongan, with customer satisfaction as a mediating variable. This study uses a quantitative method with a descriptive approach and Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis technique. A sample of 100 respondents was purposively selected, namely active Shopee users in the Lamongan area. The results show that trust has a positive and significant influence on customer loyalty and customer satisfaction. This means that the higher the level of customer trust in the Shopee platform, the higher the level of satisfaction and loyalty formed. On the other hand, promotion through Word of Mouth has also been shown to have a significant influence on customer loyalty. Customers tend to be more loyal when receiving positive recommendations from others or their surroundings. However, WOM promotion does not have a direct influence on customer satisfaction, which means that promotion alone is not enough to increase satisfaction if it is not accompanied by other factors such as service quality and user experience. Furthermore, the mediation analysis shows that customer satisfaction is not a mediator in the relationship between WOM promotion and customer loyalty. This means that loyalty can be formed directly through word-of-mouth promotion without prior satisfaction. Conversely, customer satisfaction has been shown to partially mediate the effect of trust on customer loyalty. This confirms that building trust can create satisfaction, which ultimately strengthens loyalty. These findings suggest that to increase customer loyalty, companies need to focus on enhancing user trust through reliable and consistent service. Furthermore, word-of-mouth promotion management also needs to be optimized as an effective marketing strategy. These conclusions can serve as guidelines for businesses in developing marketing strategies oriented toward customer satisfaction and loyalty.